Analisis Hukum Terhadap Pelaksanaan Adopsi Anak Dalam Sudut Pandang Hukum Positif Pada Putusan Nomor 29/Pdt.P/2021/PA.Dbs - Henna Kurniasih; Gunawan Djajaputra (UNES Law Review, 2024)
The practice of child adoption has existed since ancient times. In the past, particularly among couples who had not been blessed with offspring by God, it was common to adopt a child who was still a relative, albeit a distant one. Consequently, child adoption in those times was not based on legal regulations, as the adopted child remained within the family. Therefore, the legality of adoption was not a significant concern in the past. The issues addressed in this paper include the factors and evidence considered by judges in granting adoption petitions and the regulations regarding child adoption under positive law in Indonesia. The research method employed is normative juridical, which involves legal research conducted through the examination of library materials, also known as library research. The findings reveal that the panel of judges considers several points of law, primarily the judges' conviction to grant the petitioners' request based on various pieces of evidence presented during the trial, including testimonies from the biological parents of Child X and witnesses from the relatives of Petitioner I and Petitioner II. The implementation of child adoption in Indonesia is based on the Child Protection Law and Government Regulation No. 54 of 2007 on Child Adoption, which stipulate that the adoption process involves several requirements and is carried out to meet the needs and best interests of the child.